Wiara jako synteza słuchania i widzenia według Lumen fidei - Moskałyk, Jarosław (Poznańskie Studia Teologiczne, 2014)
Pope Francis in his encyclical reminded us that Lumen fidei contains abundant material truth about the need of the development of a comprehensive religious awareness based on man’s inborn senses. Simultaneously he pointed at their grounding and fulfillment in a person’s practical choices, particularly those pertaining to confidence in and faithfulness to God. Here actual exercise of the attributes of listening and seeing opens the prospect of the perception of something more besides the materially discernible object. This creates the possibility of bringing closer to view the supernatural reality, and at the same time frees a person from a unilateral attachment to transient values. Finally, the gift of listening and seeing performs the only and unique function of actively enriching the inner life of the individual human with the presence and action of God.